2011
DOI: 10.1021/jp2014034
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Effects in DNA Microarrays: A Multiplatform Study

Abstract: It has recently been shown that in some DNA microarrays the time needed to reach thermal equilibrium may largely exceed the typical experimental time, which is about 15h in standard protocols (Hooyberghs et al. Phys. Rev. E 81, 012901 (2010)). In this paper we discuss how this breakdown of thermodynamic equilibrium could be detected in microarray experiments without resorting to real time hybridization data, which are difficult to implement in standard experimental conditions. The method is based on the analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A previous study [9] in which hybridizing strands were 30-mers did not provide a single straight line in a ln I versus ∆∆G plot. Deviations due to lack of thermodynamic equilibrium were observed in the high-intensity ranges, as discussed in [11,13].…”
Section: A Nearest-neighbor Parameters From Linear Regressionmentioning
confidence: 87%
“…A previous study [9] in which hybridizing strands were 30-mers did not provide a single straight line in a ln I versus ∆∆G plot. Deviations due to lack of thermodynamic equilibrium were observed in the high-intensity ranges, as discussed in [11,13].…”
Section: A Nearest-neighbor Parameters From Linear Regressionmentioning
confidence: 87%
“…The real problem lies in assays of heterogeneous ssDNA targets where diverse sequences, lengths, mixed target and non-target concentrations and possible mismatch duplex co-equilibria confound approaches to a single equilibrium assay endpoint. [203, 211, 212]. Incubation times often vary, different even for similar concentrations of probe and target, but depending on assay conditions and largely influenced by ssDNA probe density distributions and ssDNA sequence and length.…”
Section: Microarray Surface-capture Assay Kineticsmentioning
confidence: 99%
“…These studies suggested the feasibility of electrostatic control for DNA hybridization and design of assays to avoid DNA secondary structure folding problems (i.e., self complimentarity). [212] They used linear Poisson–Boltzmann theory for double-layer interactions between an ion-penetrable sphere and a hard plate with variables including binding enthalpy, entropy and equilibrium reaction constants for the immobilized complex. They also developed a mean field model for Coulombic effects in two-dimensional DNA arrays to understand the binding isotherms and thermal denaturation of the double helix.…”
Section: Microarray Surface-capture Assay Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more general (and precise) model would describe the invading protein through a binding energy ε ′ different from the binding energy ε for the bound protein in case of heterogeneous replacement, as well through its number of bound units, rather than the on/off description used here. Binding/unbinding of small DNA fragments (oligonucleotide) on a DNA under force [11] and exchange of DNA-binding oligonucleotides in DNA hybridization assays [9, 13, 14] are likely described by the Z-S-SB model. Including sequence specificity (dependence of ε on the sites) could help in modeling such experiments [12].…”
mentioning
confidence: 99%